The coracoglenoid notch: anatomy and clinical significance - Strnad, Tomáš; Bartoníček, Jan; Naňka, Ondřej; Tuček, Michal (Surgical and radiologic anatomy, 2021)
INTRODUCTION: The superior surface of the anatomical neck is presented in the classification of scapular fractures as a 2-cm-long structure, which does not correspond to reality. This issue has not yet been adequately addressed in the literature. The aim of the study was to assess the variability of a notch between the upper rim of the glenoid and the coracoid base, the so-called coracoglenoid notch (CGN), and its clinical significance. MATERIALS AND METHODS: The study was based on the examination of 204 dry bone specimens of adult scapulae (92 male and 112 female). We have determined quantitative criteria for the evaluation of the CGN type, measuring the offset of anatomical neck using a digital caliper. The findings were compared with 3D CT reconstructions of fractures of the scapular anatomical neck. RESULTS: Three basic types of CGN have been identified: type A-a well-developed notch in 31%, type B-a shallow notch in 53% and type C-an absent notch in 16%. No significant difference in CGN was found between the sexes, or between the right and left sides. When compared with our six cases of the anatomical neck fracture of the scapula, two patients displayed CGN type A and type B, respectively; but in four patients, it was impossible to distinguish between types A and B. CONCLUSION: The study has documented a high variability of CGN. Its presentation in the classification schemes does not correspond to anatomical reality. The presence of a deep, or shallow, notch may constitute an anatomical predisposition to a fracture of the anatomical neck.
Keywords: počítačová rentgenová tomografie; fraktury kostí; anatomická variace; Scapula; Humans; lidé středního věku; Female; Aged; mladý dospělý; dospělí; senioři; lidé; Adult; ženské pohlaví; Male; Middle Aged; lopatka; Fractures, Bone; Tomography, X-Ray Computed; Adolescent; Aged, 80 and over; Young Adult; senioři nad 80 let; mužské pohlaví; Anatomic Variation; mladiství